Telemedicine Practice Guidelines and Telepsychiatry Operational Guidelines, India—A Commentary. Issue 5 (October 2020) - Dinakaran, Damodharan; Basavarajappa, Chethan; Manjunatha, Narayana; Kumar, Channaveerachari Naveen; Math, Suresh Bada
Recent advancements in technology, access to smartphone, and gains achieved in increased internet speed and data transfer have expanded the scope of health care service delivery through the digital platforms. In India, telemedicine services remain poorly adopted and integrated due to various barriers. The important reasons are lack of legal and administrative clarity in using technology for service delivery and inertia from health service providers to adopt newer developments. However, during coronavirus disease (COVID-19) pandemic, these equations are changing. The Telemedicine practice guidelines released in March, 2020, and Telepsychiatry operational guidelines released in May, 2020, appear to remove these barriers and promote equitable access to health care. In this article, the authors discuss the scope of these guidelines.